Differences in image-enhanced endoscopic findings between Helicobacter pylori-associated and autoimmune gastritis - Kato, Minoru; Uedo, Noriya; Toth, Ervin; Shichijo, Satoki; Maekawa, Akira; Kanesaka, Takashi; Takeuchi, Yoji; Yamamoto, Sachiko; Higashino, Koji; Ishihara, Ryu; Nemeth, Artur; Thorlacius, Henrik; Tomita, Yasuhiko; Wurm Johansson, Gabriele (Endoscopy International Open, 2021)
Background and study aims The aim of this study was to elucidate the differences in image-enhanced endoscopy (IEE) findings between Helicobacter-pylori-associated and autoimmune gastritis.Patients and methods Seven H. pylori-naïve, 21 patients with H. pylori-associated gastritis and seven with autoimmune gastritis were enrolled. Mucosal atrophy in the corpus was evaluated using autofluorescence imaging and classified into small, medium and large. In a 2 × 2-cm area of the lesser curvature of the lower corpus, micromucosal pattern was evaluated by magnifying narrow band imaging and proportion of foveola (FV)- and groove (GR)-type mucosa was classified into FV > 80 %, FV 50 % to 80 %, GR 50 % to 80 %, and GR > 80 %, then a biopsy specimen was taken.Results Fifteen of 21 (71 %) H. pylori-associated gastritis patients exhibited medium-to-large atrophic mucosa at the corpus lesser curvature. All autoimmune gastritis patients had large atrophic mucosa throughout the corpus (P < 0.001). All H. pylori-naïve patients had the FV > 80 % micromucosal pattern. Nineteen of 21 (90 %) H. pylori-associated gastritis patients had varying proportions of GR- and FV-type mucosae and five of seven (71 %) autoimmune gastritis patients showed FV > 80 % mucosa (P < 0.001). Compared with patients who were H. pylori-naïve, patients with H. pylori-associated and autoimmune gastritis exhibited a higher grade of atrophy (P < 0.001), but only patients with H. pylori-associated gastritis showed a higher grade of intestinal metaplasia (P = 0.022). Large mucosal atrophy with FV > 80 % micromucosal pattern had sensitivity of 71 % (95 % CI: 29 %–96 %) and specificity of 100 % (95 % CI: 88 % to 100 %) for diagnosis of autoimmune gastritis.Conclusions IEE findings of the gastric corpus differed between H. pylori-associated and autoimmune gastritis, suggesting different pathogenesis of the two diseases.